The Impact Of Cooperative Integrated Reading And Composition (Circ) Method Of Pharagraf Competence Understanding Of Vii Grader Students - Muh. Tauiq; Zainul Muttaqin (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2019)
The objective 0f the study to know The Effect Of Cooperative Integrated Reading And Composition Model (CIRC) Toward Comprehending paragraph Skill For The Seventh Year Students of MTs Darul Hikmah Lebui In The School Year 2018/2019.the target of population were all of the seventh year students of mts. Darul Hikmah Lebui the number of 37 students that consist of two classes.the writer considered to take the sample of this study class VII a 20 students as the experimental groups class and VII b 17 students as the control groups. The instruments which were developed to collect data were comperehending paragraph test. To obtain the data of the study the writer was used test in the form of essy tests, and it consist of 5 items at the experimental groups and the contol groups at paragraph reading skill. In hypothesis testing was used quantitative test (t-test). The result of the data analysis was found t-test was 1,862, the the result analiysis t-table at level significance 5% and dk 35 was found t-table was 2,042 t-table in significance rank 5% it,s mean that in hypothesis testing which was discussed at previous chapter that ho was rejected ha wa accepted. On the opher word, there was significant effect Of Cooperative Integrated Reading And Composition Model (CIRC) toward comprehending paragraph skill for the seventh year students of MTs Darul Hikmah Lebui In The School Year 2018/2019.